2018
DOI: 10.1007/s12264-018-0274-y
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Mechanisms Underlying Arterial Baroreceptor Remodeling in Cardiovascular Diseases and Diabetes

Abstract: Clinical trials and animal experimental studies have demonstrated an association of arterial baroreflex impairment with the prognosis and mortality of cardiovascular diseases and diabetes. As a primary part of the arterial baroreflex arc, the pressure sensitivity of arterial baroreceptors is blunted and involved in arterial baroreflex dysfunction in cardiovascular diseases and diabetes. Changes in the arterial vascular walls, mechanosensitive ion channels, and voltage-gated ion channels contribute to the atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 217 publications
1
24
0
1
Order By: Relevance
“…Some endogenous factors (such as angiotensin II and superoxide anion) can modulate these morphological and functional alterations through intracellular signaling pathways in impaired arterial baroreceptors. It has been suggested that arterial baroreceptors could serve as a potential therapeutic target to improve the prognosis of patients with diabetes and cardiovascular diseases (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some endogenous factors (such as angiotensin II and superoxide anion) can modulate these morphological and functional alterations through intracellular signaling pathways in impaired arterial baroreceptors. It has been suggested that arterial baroreceptors could serve as a potential therapeutic target to improve the prognosis of patients with diabetes and cardiovascular diseases (16).…”
Section: Discussionmentioning
confidence: 99%
“…Impairment of baroreflex mechanisms resulting in a chronic adrenergic activation often accompanies cardiovascular disease. A blunted baroreflex gain is predictive of increased cardiovascular risk in patients with myocardial infarction and heart failure (11,16). Evidence has also emerged suggesting that BRS could be a marker of CAN in patients with longer-term diabetes (17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…It has been suggested that transient receptor potential (TRP) channels through their Ca 2+ entry, release, and extrusion mechanisms in membranes regulate VSMC contraction known as vasoconstriction response. Theoretically, Ca 2+ influx through these channels may directly activate contractile process, but this needs more experimental evidence [68,69]. Moreover, considering the role of transient receptor potential (TRP) channels in VSMC phenotype switching and vasoconstriction, we tried to find out whether Mcoln1 gene deletion contributes to arterial stiffness in mice [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of fluctuations in blood pressure and heart period represents another parameter of clinical importance as risk marker for cardiovascular morbidity and mortality (La Rovere et al, 2011 ), especially in some cardiac (Malberg et al, 2002 ) and non-cardiac diseases (Bär et al, 2007 ) or after specific therapeutic procedures (Acampa et al, 2011 ), that are able to determine changes at different levels, including arterial vascular walls, mechanosensitive ion channels, and voltage-gated ion channels (Tu et al, 2019 ). However, spontaneous baroreflex indices don't clearly reflect arterial baroreflex gain (Lipman et al, 2003 ); for this reason, Wessel et al tested whether the xBRS method (Wesseling et al, 2017 ) is suitable to quantify the baroreflex sensitivity from non-invasive, non-interventional measurements under resting conditions.…”
mentioning
confidence: 99%